A Vascular Variation in Radial Forearm Free Flap Harvesting: Distal Branching of the Radial Artery—A Case Report. (31st August 2021) - Wüster, Jonas; Beck-Broichsitter, Benedicta; Koerdt, Steffen; Heiland, Max; Goedecke, Maximilian
Study Design: Case report. Objective: By reporting such a rare vascular variation of the radial artery, we aim to make other surgeons aware of comparable vascular variations in radial forearm free flap harvesting. Methods: In this case report, we present an 84-year-old male patient, with a rare distal branching of the radial artery into the deep palmar branch, approximately 7 cm from the wrist. In order to visualize the vascular variation, intraoperative photo documentation took place. Results: The radial free flap harvesting was successful and no postoperative complications were noted. Conclusions: Distal branching of the radial artery into the deep palmar branch may occur in radial forearm free flap harvesting. Since no restrictions in flap perfusion and/or hand perfusion were observed in our case, we recommend radial forearm free flap raising in the traditional way. No changes concerning the design and the positioning of the skin paddle need to be made.